10th National Technical Seminar on Underwater System Technology 2018 (NUSYS’18) - Zainah, Md. Zain (2018)
The 10th National Technical Seminar on Underwater System Technology 2018 (NUSYS’15) was organized by Faculty of Electrical and Electronics Engineering, Universiti Malaysia Pahang on the 26-27 September 2018 at the Library, Universiti Malaysia Pahang, Pekan Campus, Pahang, Malaysia. For this year, “Deeper Discoveries” was selected as the NUSYS’18 theme. NUSYS’18 was jointly organized by IEEE Oceanic Engineering Society (IEEE OES) Malaysia Chapter, Malaysian Society for Automatic Control Engineers (MACE) IFAC NMO and Institute of Engineer Malaysia (IEM) Marine Engineering and Naval Architecture Technical Division (MNATD).